Newton's laws as an interpretive framework in system dynamics. (27th February 2018) - Hayward, John; Roach, Paul A.
Abstract: This paper proposes an interpretative framework for system dynamics models using concepts from Newtonian mechanics. By considering the second derivative form of a model, it is shown that Newton's three laws of motion have their equivalent in system dynamics, with forces between stocks being determined using the loop impact method. The concepts of mass, inertia, momentum and friction are explored as to their usefulness in understanding model behaviour. The Newtonian framework is applied to two standard system dynamics models—inventory–workforce and economic long‐wave—where their behaviour is analyzed using force dominance on the stocks. Results show improved intuitive understanding of system behaviour compared with existing dominance methods, particularly for models with exogenous effects, oscillations and many loops. The framework is commended for further exploration. Copyright © 2018 System Dynamics Society